IMPLEMENTASI LESSON STUDY PADA METODE NUMBERED HEADS TOGETHER DIPADU DENGAN TEAM GAMES TOURNAMENT UNTUK PENGEMBANGAN KARAKTER SISWA KELAS X SMA NEGERI 1 KEPANJEN - Agil Lepiyanto (Bioedukasi Jurnal Pendidikan Biologi, 2012)
An action research, with the implementation of lesson study in numbered heads together method combined with team games tournament method for character development, the increasing of learning activity, motivation, and the students’ learning achievement in biology at SMA Negeri 1 Kepanjen, is done with the purpose to develop the character of the students in learning biology. The implementation of Numbered Heads Together is combined with Team Games Tournament and it can develop students’ characters. The indicator of friendship has increased until 5.07% from cycle I to cycle II and has increased again in cycle III as much as 17.51%. The indicator of discipline has increased until 4.03% from cycle I to cycle II and has increased again in cycle III as much as 13.13%. The indicator of work hard has increased until 8.69% from cycle I to cycle II and has increased again in cycle III as much as 10.48%. The indicator of students’ independent has increased until 9.67% from cycle I to cycle II and has increased again in cycle III as much as 9.79%. Kata kunci: Lesson study, Numbered Heads Together, Team Games Tournament, Karakter Siswa